Landau Kleffner Syndrome and Misdiagnosis of Autism Spectrum Disorder: A Mini-Review - Zafari, Ali; Karimi, Nasim; Taherian, Mahdi; Taherian, Reza (International Clinical Neuroscience Journal, 2018)
Autism spectrum disorders (ASD) is the name for a group of developmental disorders including a wide range of signs, symptoms and disability. Landau kleffner syndrome (LKS) or acquired epileptic aphasia is a pediatric disorder characterized by the association of epileptiform electroencephalographic (EEG) abnormalities and acquired aphasia. The early stages of the LKS may be manifested by the symptoms of the autism leading to misdiagnosis. Since LKS is a progressive disease, its misdiagnosis leads to a greater neurocognitive deterioration which may result in seizure in the final stages. The purpose of this review was to provide an overview of available researchs on ASD population and patients with LKS and relationship between these two diseases.